(untitled) (Journal of Engineering, 2020)
The main aim of this paper is studied the punching shear and behavior of reinforced concrete slabs exposed to fires, the possibility of punching shear failure occurred as a result of the fires and their inability to withstand the loads. Simulation by finite element analysis is made to predict the type of failure, distribution temperature through the thickness of the slabs, deformation and punching strength. Nonlinear finite element transient thermal-structural analysis at fire conditions are analyzed by ANSYS package. The validity of the modeling is performed for the mechanical and thermal properties of materials from earlier works from literature to decrease the uncertainties in data used in the analysis. A parametric study was adopted in this study, it has many factors such as the ratios of length to thickness, fire temperature, time exposed to fire, concrete compressive strength, area exposed to fires and type of support. It can be concluded from this research the significant factors that affect the punching shear strength. However, the increasing ratio of length to thickness may be lead to increasing the deflection more than 123% at fire condition. Also, the increasing temperature leads to increasing the deflection about 40% at fire condition.